2011
DOI: 10.1186/1471-2407-11-93
|View full text |Cite
|
Sign up to set email alerts
|

Integrated mutation, copy number and expression profiling in resectable non-small cell lung cancer

Abstract: BackgroundThe aim of this study was to identify critical genes involved in non-small cell lung cancer (NSCLC) pathogenesis that may lead to a more complete understanding of this disease and identify novel molecular targets for use in the development of more effective therapies.MethodsBoth transcriptional and genomic profiling were performed on 69 resected NSCLC specimens and results correlated with mutational analyses and clinical data to identify genetic alterations associated with groups of interest.ResultsC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
4
9
0
Order By: Relevance
“…Reasons for the lower number of significant genes in the independent cohorts likely include smaller sample sizes and different microarray platforms compared with the discovery cohorts. The low number of differentially expressed genes between the mutation groups (only 21 genes consistently differentially expressed in all five discovery cohorts) is similar to results from other studies [8,12,14,16]. This low number of differentially expressed genes argues against that the mutational subgroups represent distinct transcriptional groups.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Reasons for the lower number of significant genes in the independent cohorts likely include smaller sample sizes and different microarray platforms compared with the discovery cohorts. The low number of differentially expressed genes between the mutation groups (only 21 genes consistently differentially expressed in all five discovery cohorts) is similar to results from other studies [8,12,14,16]. This low number of differentially expressed genes argues against that the mutational subgroups represent distinct transcriptional groups.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have reported KRAS mutant signatures or differentially expressed genes between adenocarcinomas with EGFR and/or KRAS mutations and respective wild type cases [8,10,12,14,16,26,33,40]. However, the overlap between these public signatures is very poor when directly compared (Figures S3B and C).…”
Section: Discussionmentioning
confidence: 99%
“…In another study of KRAS and EGFR mutations in adenosquamous lung carcinoma, one out of three tumors had an EGFR mutation detected only in the glandular (adeno) component and not in the squamous component [16]. This is not surprising as lung adenocarcinomas and lung squamous cell carcinomas have markedly different genomic and gene expression profiles [17,18]. In accordance with Swanton's trunk and branch evolutionary model [7], the two histotypes could have diverged from their pluripotential stem cell origin by the acquisition of an EGFR mutation in one subclone (leading to invasive adenocarcinoma), but a different genomic event in the eventual squamous or pleomorphic component.…”
Section: Discussionmentioning
confidence: 99%
“…1) and silencing of gene expression [17]. Studies have also found that SHOX2 gene hypermethylation was accompanied by other genomic rearrangements, such as increased gene copy number and amplification [14,16,49], while the amplification did not lead to an increase in SHOX2 gene expression. This observation suggests that multiple abnormalities exist in lung cancer, while the precedence relationship and causality of these abnormalities are not clear yet.…”
Section: Relationship Between Shox2 Gene Methylation and Lung Cancermentioning
confidence: 94%